Analisis Kesalahan (Error Analysis) Hasil Terjemahan Teks Inggris ke Indonesia Oleh Mahasiswa Politeknik Negeri Cilacap - Betti Widianingsih (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2019)
This research aims to find out and describe type of error employed by students in translating english text into indonesian text. The author used qualitative research approach to describe type of translation The step of the data analysis consists of 1) recognition; 2) description; 3) explanation; 4) evaluation and 5) correction. From the result of the research, there were 284 errors employed by students from 3 study programs. Based on the taxonomy of perfomation category, it was found that there were 4 types of errors employed by the students of State Polytechnic of Cilacap, i.e., omission 33 data (11,61%), addition 15 data (5,28%), misformation 197 data (69,36%) and misordering 39 data (13,73%). From the findings, it can be concluded that Electrical Engineering students often did errorsin translating, especially misformation. Keywords : word, phrase, clause, translation, error analysis